(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Corruption, characterized as the abuse of entrusted power for personal gain, has far-reaching and damaging effects on societies. Moreover, corruption undermines the rule of law, resulting in human rights violations, market distortions, diminished quality of life, and the proliferation of organized crime, terrorism, and other threats to human security. Corruption is a transnational phenomenon that affects all societies and economies, making international cooperation to prevent and control it essential. This research paper thoroughly investigates the extensive impacts of corruption, including the erosion of trust, impeded economic development, exacerbated inequality, poverty, and social divisions. It also aims to identify and examine various factors that contribute to corruption. These factors encompass gluttony, opportunistic circumstances, and temptations arising from party finances and patronage, fear of losing power, and the necessity for additional funds to uphold certain standards. Additionally, the paper provides a comprehensive analysis of the legal framework addressing corruption in India, shedding light on existing measures and their effectiveness. Furthermore, it proposes specific measures to tackle corruption and mitigate its adverse consequences within the Indian context.